Large variability of O3-precursor relationship during severe ozone polluted period in an industry-driven cluster city (Zibo) of North China Plain. (20th September 2021) - Li, Kangwei; Wang, Xinhua; Li, Liming; Wang, Jian; Liu, Yingying; Cheng, Xiang; Xu, Bo; Wang, Xiuyan; Yan, Peng; Li, Shijie; Geng, Chunmei; Yang, Wen; et al.
Abstract: Zibo, a highly industrialized cluster city in the central area of the North China Plain (NCP), has suffered from serious ozone pollution in recent years. In this study, a comprehensive field campaign was conducted during July 2019 at three representative and diversified areas in Zibo, including two suburban sites (Tianzhen (TZ) and Xindian (XD)) and one urban site (Beijiao (BJ)). The O3 variation patterns were overall similar among the three sites, while its precursors (i.e. volatile organic compounds (VOCs) and nitrogen oxides (NOx )) showed distinct site-to-site differences. A 0-D box model incorporating the latest Master Chemical Mechanism (MCMv3.3.1) was applied using observations as constraints, and NOx -limited, VOC-limited and transitional regimes were generally identified for TZ, BJ and XD respectively, particularly during high-O3 episodes. We believe that such large variability of O3 -precursor relationship found in Zibo may exist widely in many other cities, which challenges the current O3 pollution control. It was further concluded that both high in-situ O3 production rate (daytime peak 21–27 ppbv h −1 ) and O3 transported from residual layer are responsible for the high ground-level O3 . Detailed mechanism modelling with many scenarios suggested that a synergic reduction plan for NOx and VOC would be the most feasible and effective option to achieve O3 -attainment levels. It is suggested that the minimum reduction in NOx should be by more than 40% (TZ), 60% (BJ) and 20% (XD), while anthropogenic VOC should simultaneously be cut more than 60% (TZ), 40% (BJ) and 60% (XD). Our fundamental chemical mechanism modelling provided an improved understanding of O3 -precursor relationship, and the derived policy-relevant guidance can assist the local government like Zibo to deal with O3 challenge. These results could also provide insights for regional O3 control across the North China Plain. Highlights: The characteristics of O3 and its precursors were investigated during 2019 summertime in Zibo. 0-D box model showed a large variability of O3 -precursor relationship in spatial-temporal scales over Zibo. Both strong local photochemistry and residual layer transport contributed to high ground-level O3 . A synergic reduction plan for NOx and VOC was developed to achieve O3 -attainment levels.